Strategi Pengelolaan Kepemimpinan dan Perubahan Organisasi - Yusnita, Reni; Aslami, Nuri (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This study aims to determine the leadership and change management prosedures in an organization. The type of research conducted is a literature study, which aims to collect books and data and other written information related to the discussion of the problem under study. Sources of data from books, magazines and articles. Data collection was carried out using a literature search method using primary legal materials and secondary legal materials. Legal materials will be investigated and analyzed using the approach used in this investigation to answer legal questions in this investigation. The research results of prosedures to lead change are 1) accelerating change in the future, 2) leading the vortex of change, 3) taking steps to lead change, 4) change and sustainability) to increase employee satisfaction. Prosedures for implementing change for successful change include 1) annual goals, 2) guidelines, 3) resource allocation, 4) competitive management, 5) structural coordination with change prosedures, and 6) Management resistance, 7) creating a culture that support change strategy, 8) Linking performance with reward strategy 9) Considering human resources in implementing change strategy.